Cover Picture: Discovery of Elusive K4O6, a Compound Stabilized by Configurational Entropy of Polarons (Angew. Chem. Int. Ed. 1/2019). Issue 1 (12th December 2018) - Freysoldt, Christoph; Merz, Patrick; Schmidt, Marcus; Mohitkar, Shrikant; Felser, Claudia; Neugebauer, Jörg; Jansen, Martin
Abstract : Discovery of elusive K 4 O 6 an endothermic mixed peroxide–superoxide compound: In the Communication onpage 149, M. Jansen et al. report on the synthesis of K4 O6 that owes its stability to the configurational entropy of polarons, and thus exists only above a distinct temperature threshold. The puzzling speed at which the all‐solid‐state reactions of formation and decomposition proceed, as a function of temperature, are illustratively documented by areal‐time video .